« Là où on nous attend le moins ». L’animal comme fiction d’investigation architecturale - Dominique Rouillard (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
This article draws on six years of a master-level seminar at the ENSA Paris Malaquais, from September 2015 to June 2021, around the question of “the other animal in architecture”. Developed as part of a long-term research project, this question was introduced as a learning tool for disaccustoming in thinking and theorizing architecture (the city, the territory), as well as an initiation to ecological and environmental issues: the animal as a theoretical and surreal fiction in research.To this end, students were placed in the uncomfortable position of rejecting currently existing hypotheses surrounding the animal in the context of “biodiversity loss”, which have been gradually reaching schools of architecture, and even renouncing the thousand-year history of the relationship between architecture and the animal. In doing so, this may allow them to encounter the other animal of architecture, “where we least expect the”.